2019
DOI: 10.1093/hmg/ddz119
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic mutations in the ALS gene CCNF cause cytoplasmic mislocalization of Cyclin F and elevated VCP ATPase activity

Abstract: Amyotrophic lateral sclerosis (ALS) is an adult-onset motor neuron disease characterized by a progressive decline in motor function. Genetic analyses have identified several genes mutated in ALS patients, and one of them is Cyclin F gene (CCNF), the product of which (Cyclin F) serves as the substrate-binding module of a SKP1–CUL1–F-box protein (SCF) ubiquitin ligase complex. However, the role of Cyclin F in ALS pathogenesis has remained unclear. Here, we show that Cyclin F binds to valosin-containing protein (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…In contrast, a recent study that screened 48 patients with FTD reported identified 3 mutations that lie within the D1 domain of VCP and are hypothesized to affect ATPase binding activity (Wong et al, 2018). Interestingly, it has been reported that VCP interacts with FUS (ALS6) (Wang et al, 2015) and Cyclin F (CCNF) (proposed FTDALS5) (Yu et al, 2019) both of which are implicated in ALS. Mutations in FUS/CCNF were shown to increase ATPase activity of VCP in the cytoplasm, causing VCP to mislocalize to the cytoplasm (Yu et al, 2019) and trigger accumulation of polyubiquitinated proteins (Wang et al, 2015).…”
Section: Als14: Valosin Containing Protein (Vcp)mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, a recent study that screened 48 patients with FTD reported identified 3 mutations that lie within the D1 domain of VCP and are hypothesized to affect ATPase binding activity (Wong et al, 2018). Interestingly, it has been reported that VCP interacts with FUS (ALS6) (Wang et al, 2015) and Cyclin F (CCNF) (proposed FTDALS5) (Yu et al, 2019) both of which are implicated in ALS. Mutations in FUS/CCNF were shown to increase ATPase activity of VCP in the cytoplasm, causing VCP to mislocalize to the cytoplasm (Yu et al, 2019) and trigger accumulation of polyubiquitinated proteins (Wang et al, 2015).…”
Section: Als14: Valosin Containing Protein (Vcp)mentioning
confidence: 99%
“…Recently, a CCNF mutation in a zebrafish model has been shown to have disrupted axonal outgrowth (Galper et al, 2017;Hogan et al, 2017). Further support for CCNF as an ALS-FTD gene comes from the finding that CCNF interacts with valosin containing protein (VCP) (ALS14), increasing VCP's ATPase activity, which in turn promotes TDP-43 aggregation (Yu et al, 2019). Thus, for the purposes of this review, CCNF is described as FTDALS5.…”
Section: Cyclin F (Ccnf)mentioning
confidence: 99%
See 1 more Smart Citation
“…CCNF encodes a protein called cyclin F, a binding partner of another ALS-associated protein VCP. A recent study demonstrated that, in cell culture, CCNF mutations may contribute to ALS pathogenesis by increasing the ATPase activity of VCP in the cytoplasm, which in turn increases TDP-43 aggregation [47].…”
Section: Proteostasismentioning
confidence: 99%
“…Other rare or even novel variants have been identified in other cohorts, but none of them have been recurrent or shown to segregate with disease. Mutations reported in ALS do not alter cyclin F stability or disrupt formation of the SCF complex [47], but in vitro can increase the ATPase activity of VCP (another ALS-causative gene) while others impair ubiquitin-mediated proteasomal degradation [47]. Either mechanism disrupts the normal processing of TDP-43, leading to its abnormal cytoplasmic accumulation [47,81].…”
Section: Recently Discovered Als Genesmentioning
confidence: 99%